2002
DOI: 10.1590/s0101-81752002000100012
|View full text |Cite
|
Sign up to set email alerts
|

Ascocotyle (Phagicola) rara sp. n. (Digenea, Heterophyidae) from Ixobrychus exilis (Aves, Ardeidae) in Brazil

Abstract: Ascocotyle (Phagicola) rara sp. n. is described from the intestine of Ixobiyclius exilis (Gmelin, 1789), a Brazilian bittern. The new species is compared with Ascocotyle (Phagicola) angeloi Travassos, 1928 and Ascocotyle (Phagicola) moUieiiisicola (Sogandares-Bernal & Bridgman, 1960); the main distinguishing characters are related to the aspect of the gonotyl that is not perforated in A. (P.) rara sp. n. when compared to A. (P.) mollienisicola and the absence of the crown of spines at the anteriorend in the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…(P.) rara does the genital pore open dextral to the genital sac as described by Arruda et al (2002). In the present study, the terminal part of the uterus was observed to simply follow the antero-sinistral margin of the ventral sucker to open into the ventrogenital sac together with the ejaculatory duct and gonotyl (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…(P.) rara does the genital pore open dextral to the genital sac as described by Arruda et al (2002). In the present study, the terminal part of the uterus was observed to simply follow the antero-sinistral margin of the ventral sucker to open into the ventrogenital sac together with the ejaculatory duct and gonotyl (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…(P.) rara are in fact smooth, lacking any tegumental spines that were reported and illustrated by Arruda et al (2002). Actually, the outer, syncytial layer of the tegument of A.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations